2014
DOI: 10.1002/cncr.28587
|View full text |Cite
|
Sign up to set email alerts
|

Immigration factors and prostate cancer survival among Hispanic men in California: Does neighborhood matter?

Abstract: BACKGROUND Hispanics are more likely than other racial/ethnic groups in the United States to be diagnosed with later stage of prostate cancer, yet they have lower prostate cancer mortality rates. The authors evaluated the impact of nativity and neighborhood-level Hispanic ethnic enclave on prostate cancer survival among Hispanics. METHODS A total of 35,427 Hispanic men diagnosed with invasive prostate cancer from 1995 through 2008 in the California Cancer Registry were studied; vital status data were availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 40 publications
4
42
0
Order By: Relevance
“…The mortality hazard was higher in women living in low-SES neighborhoods than in the highest SES quintile. Previous breast, prostate, and lung cancer studies have also found survival associations with neighborhood SES and Hispanic enclave 37,38 ; however, our study is the first to show similar neighborhood results for cervical cancer.We found that the association of nativity and neighborhood SES on survival varied by Hispanic enclave, with survival benefits among foreign-born and survival deficits for low-SES neighborhoods seen predominantly among cases living in high Hispanic enclaves. Ethnic enclaves may offer protective effects via buffering against acculturation.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The mortality hazard was higher in women living in low-SES neighborhoods than in the highest SES quintile. Previous breast, prostate, and lung cancer studies have also found survival associations with neighborhood SES and Hispanic enclave 37,38 ; however, our study is the first to show similar neighborhood results for cervical cancer.We found that the association of nativity and neighborhood SES on survival varied by Hispanic enclave, with survival benefits among foreign-born and survival deficits for low-SES neighborhoods seen predominantly among cases living in high Hispanic enclaves. Ethnic enclaves may offer protective effects via buffering against acculturation.…”
supporting
confidence: 69%
“…The mortality hazard was higher in women living in low-SES neighborhoods than in the highest SES quintile. Previous breast, prostate, and lung cancer studies have also found survival associations with neighborhood SES and Hispanic enclave 37,38 ; however, our study is the first to show similar neighborhood results for cervical cancer.…”
supporting
confidence: 69%
“…Two commonly assessed proxy measures of exposure to Hispanic culture, patient birthplace (U.S. vs. foreign) and residence in a neighborhood with other Hispanics, have been associated with mortality. Foreign-born, compared to U.S.-born Hispanics, often have lower cancer mortality, despite worse risk factor profiles [11,12,13]. The protective effect of foreign birthplace is referred to as the Immigrant Paradox.…”
Section: Introductionmentioning
confidence: 99%
“…The protective advantages of living in high Hispanic density neighborhoods have been referred to as barrio effects [14]. Hispanics with cancer living in neighborhoods with higher Hispanic density (i.e., ethnic enclaves) may experience a survival advantage [12,13]. However, neighborhoods with large Hispanic and/or foreign-born populations also experience disproportionate socioeconomic deprivation, including concentrated poverty [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation